2018
DOI: 10.1007/s00167-018-5185-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical considerations are crucial for the success of tendon and meniscus allograft integration—a systematic review

Abstract: Purpose This systematic review intends to give an overview of the current knowledge on how allografts used for the reconstruction of cruciate ligaments and menisci are integrated and specifically perform regarding their biomechanical function. Methods Two reviewers reviewed the PubMed and Central Cochrane library with focus on the biomechanical integration of tendon ligament and meniscus allografts. The literature search was conducted in accordance with the PRISMA statement for reporting systematic reviews and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 112 publications
1
18
0
Order By: Relevance
“…7,8,21,22 Displacement of the meniscus was recorded at the actuator of the tensile testing machine at the conclusion of cycles 1, 100, 500, and 1000, similar to previous studies evaluating displacement in meniscus tissue. 7,8 On completion of the cyclic loading protocol, the menisci were pulled to failure at a rate of 0.5 mm/s. 22 Mode of failure was recorded as suture breakage, bone block failure, bone block slippage, or meniscal tissue failure.…”
Section: Biomechanical Testingsupporting
confidence: 73%
“…7,8,21,22 Displacement of the meniscus was recorded at the actuator of the tensile testing machine at the conclusion of cycles 1, 100, 500, and 1000, similar to previous studies evaluating displacement in meniscus tissue. 7,8 On completion of the cyclic loading protocol, the menisci were pulled to failure at a rate of 0.5 mm/s. 22 Mode of failure was recorded as suture breakage, bone block failure, bone block slippage, or meniscal tissue failure.…”
Section: Biomechanical Testingsupporting
confidence: 73%
“…Seitz and Durselen 120 found that the most important biomechanical properties for MAT were secure fixation and proper graft sizing. Bone plugs or bone blocks for allograft attachment were superior to circumferential suturing and were associated with chondroprotective effects.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this technique addresses key sizing and fixation factors that have been reported to directly affect meniscal function, chondroprotection, and transplant survival. [45][46][47] Finally assessments, which is thought to be related to the less invasive nature of meniscus-only techniques. However, at the 6-month study endpoint when healing and graft integration had occurred, the menisco-tibial MAT group was associated with superior outcomes, most likely due to preserved meniscal integrity and function, treatment of tibial articular cartilage pathology, and avoidance of shrinkage, extrusion, failure, or progression of joint pathology.…”
Section: Resultsmentioning
confidence: 99%
“…Fresh meniscal‐osteochondral allograft transplantation with menisco‐tibial ligament preservation allowed for resurfacing of affected tibial cartilage with intact hyaline cartilage. In addition, this technique addresses key sizing and fixation factors that have been reported to directly affect meniscal function, chondroprotection, and transplant survival 45‐47 . Finally, by replacing the damaged tibial plateau in conjunction with MAT, whole‐joint pathology is more completely addressed, which in turn mitigates the progression of cartilage damage, degradation and loss, and the associated failure of MAT.…”
Section: Discussionmentioning
confidence: 99%